Routine Surveillance Versus Independent Assessment by an Outcome Adjudication Committee in Assessing Patients for Sternal Surgical Site Infections After Cardiac Surgery. (19th January 2016) - Mertz, Dominik; Whitlock, Richard; Kokoszka, Alicia Y.; Smith, Stephanie W.; Carignan, Alex; Rehan, Muhammad; Jaffer, Iqbal H.; Alsagheir, Ali; Loeb, Mark
Abstract : Based on a cohort of 966 patients, routine surveillance data were not sufficiently accurate for use in clinical trials investigating surgical site infections. Surveillance data can only be used if adequate 90-day follow-up is provided and if cases identified by surveillance are independently reviewed by a blinded outcome adjudication committee. Infect Control Hosp Epidemiol 2016;37:600–602